(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
In this study, we explored the influence of public spending on economic growth in Nigeria by testing the neutrality/non-neutrality of recurrent expenditure, as well as checking for the effect of interaction of the two expenditure components with monetary policy (interest rate) to see how they would influence economic growth. Data which covers the period 1981 to 2021 were analyzed using the technique of Autoregressive Distributed Lag (ARDL) model which was selected based on the fact that our variables were stationary at mixed order of levels and first difference. From the ARDL bounds test, the study revealed that there is a long-run relationship among the variables in the model which prompts the estimation of the error correction model. From the result, the findings suggest that recurrent expenditure exerts a positive and significant effect on economic growth, thereby signifying the non-neutrality of the recurrent expenditure component on economic growth. Further, the interactive terms indicates that an interaction of recurrent expenditure and interest rate on economic growth generated a negative effect though its one-period lag yields a positive and significant effect. Also, the long-run result indicates that recurrent expenditure yielded a positive but insignificant effect, thereby indicating the validity of the recurrent expenditure in the long-run. This is further confirmed as it exerted a negative but insignificant effect on economic growth when interacted with monetary policy. The policy implication of the findings centres on the fact that recurrent expenditure can only be non-neutral in influencing the macroeconomy just in the short-run.